Development of e-Modules Problem Base Learning with the Help of App Mit Invetor to Increase Students' Interest in Learning - Azizah, Nunung; sukmadewi, Angela gusti ayu; Jumadi, Jumadi (Universitas Negeri Medan, 2024)
Interest in learning is crucial in the learning process. With an interest in learning, it will also be able to affect their academic abilities, and this will be one of the supporters of the success of the learning process. Judging from the importance of the function of interest in learning, the purpose of this research is to develop electronic learning media to increase students' interest in learning. The object of this research, is the students of class X MIPA 2 and X MIPA 4 SMA 1 Kalasan with a total of 70 people. This research is development research with ADDIE design. The data collection method in this study used a questionnaire method with a Likert scale. Based on the analysis, the questionnaire obtained by X MIPA 2 is 84.5% and X MIPA 4 is 86.5%. Based on this data, the questionnaire can be said to be valid, so it is feasible to use it to increase student interest in learning. Keywords: interest in learning; electronic learning